Recent updates on treatment patterns in patients with treated attention-deficit/hyperactivity disorders from a nationwide real-world database in South Korea - Cho, Yoon; Kim, Ah Young; Lee, Sukhyang; Lee, Hankil (International Clinical Psychopharmacology, 2024)
The prevalence of attention-deficit/hyperactivity disorder (ADHD) is steadily increasing across Korea. We analyzed ADHD patients with ADHD medications (Rx) characteristics and treatment patterns compared to patients without Rx and identified the differences between pediatric-/adult- and active-/transient-patients with Rx. Using a nationwide claims dataset from 2020 to 2021, we conducted a prevalence-based cross-sectional study and analyzed the recent patients' characteristics and patterns among ADHD patients. Among 132 017 ADHD patients with Rx, differences from 20 312 without Rx across all characteristics except sex. We found significant differences in characteristics and treatment patterns between pediatric-/adult- and active-/transient-patients with Rx. Age-specific sex ratios notably diverged in pediatric patients (61.2%), but remained similar in adults, revealing significant psychiatric comorbidities differences. Active-patients peaked at 6-11 years (41.4%), while transient-patients at 18-30 years (36.1%). Predominantly, methylphenidate (89.7%), atomoxetine (27.8%), and clonidine (2.8%) were prescribed, with 85% experiencing treatment changes within methylphenidate formulations. In pediatric patients, extended-release methylphenidate was preferred (56.1%), adults favored oral delivery system methylphenidate (71.5%), and active-patients had higher treatment rates than transient-patients across all patterns, with low monotherapy rates. This study provides epidemiologic insights into recent characteristics and treatment patterns of ADHD patients with Rx in Korea, providing valuable evidence for identifying those actively receiving ADHD treatment in future healthcare policy decisions.
Keywords: Adolescent; Adult; Atomoxetine Hydrochloride; Attention Deficit Disorder with Hyperactivity; Central Nervous System Stimulants; Child; Child, Preschool; Clonidine; Cross-Sectional Studies; Databases, Factual; Female; Humans; Male; Methylphenidate; Middle Aged; Practice Patterns, Physicians'; Prevalence; Republic of Korea; Young Adult; attention-deficit hyperactivity disorder; drug utilization; methylphenidate; prevalence; South Korea